Diffraction of H-polarized wave by planar venetian-blind type grating - Калиберда, М.Е.; Литвиненко, Л.Н.; Погарский, С.А. (Radiotekhnika, 2019)
Diffraction of the plane H- polarized electromagnetic wave by finite graphene venetian-blind type grating is considered. The operator equations with respect to the spectral functions of the scattered field are presented. The reflection operator of a single graphene strip is obtained with the use of the method of singular integral equations. The dependencies of the total scattering and absorption cross section vs. frequency are represented.